(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper explores the interrelation of fantasy, dream, and reality through the lens of Lacanian psychoanalysis in literary studies. Jacques Lacan’s theories provide a nuanced understanding of the symbolic, imaginary, and real orders, offering a structuralism approach to analyzing literary texts. This research delves into how Lacanian psychoanalysis elucidates the role of fantasy as a mediator between the unconscious and reality, and how dreams serve as representations of latent desires. Through a close reading of literary works, this paper demonstrates how Lacanian concepts, such as the mirror stage, the objet petit a, and the real, contribute to a deeper comprehension of narrative structures and character psychology. This study affirms the relevance of Lacanian psychoanalysis in deconstructing literary representations of human subjectivity and the interplay between the conscious and unconscious mind.